Effects of nitrogen and water addition on soil carbon, nitrogen, phosphorus, sulfur, and their stoichiometry along soil profile in a semi-arid steppe - Guoxiang Niu; Buqing Zhong; Ruzhen Wang; Yiqian Jin; Yinliu Wang; Xiaotao Lü; Yong Jiang; Jianhui Huang (Journal of Soils and Sediments, 2023)
Purpose Although past studies have found well-constrained soil carbon (C)/nutrient ratios, the effects of increased nitrogen (N) and water inputs on these ratios across soil depths have rarely been assessed in semi-arid grasslands. Methods In this study, we evaluated the contents of total C, N, phosphorus (P), sulfur (S), and their stoichiometric ratios in a 0–80 cm soil profile following 13 years of successive N (at rates of 5 and 15 g m −2 yearr −1 ) and water addition (180 mm per growing season) in a semi-arid grassland of the Mongolian Plateau. Results In the 0–10 cm soil layer, long-term N addition tended to increase total C and N contents but decreased soil total P and S contents compared to the control. The effects of N addition, as observed in 0–10 cm soil, however, were not consistent with that in the deep 10–80 cm soil layers. Water addition increased the total C, N, and P contents across the entire soil profile but increased total S content only in 0–40 cm soil. Moreover, the combined addition of N and water generally had stronger effects on the four elements across the whole soil profile. For the stoichiometry of the four elements, a low rate of N addition (5 g m −2 year −1 ) increased soil C:N ratios and decreased soil P:S ratios in the 0–80 cm soils, but a high rate of N addition (15 g m −2 year −1 ) produced the opposite effect. Both N addition rates resulted in an increase in the soil C:P, C:S, N:P, and N:S ratios. Similarly, in plots that received water, water addition alone decreased the soil C:N ratios, while N addition caused higher fluctuations in these six elemental ratios. However, there was no consistent pattern of change in any one ratio, independent of the addition of water, when taking into account N addition rates and soil depths. Conclusion Our findings showed that the effects of N addition on soil total C, N, P, and S contents and their stoichiometric ratios were highly influenced by the rate of N addition and the depth of soil, and that these effects could be modulated by increasing precipitation. These results need to be carefully considered while managing the ecological environment in semi-arid steppes.